Mathematical Study of Effect of Temperature on Transmission Dynamics of Dengue Disease - Kafle, Jeevan; Bayalkoti, Prakash; Phaijoo, Ganga Ram (Journal of Nepal Mathematical Society, 2023)
Dengue fever is found in tropical and subtropical regions around the world. It is a vector-borne disease that is transmitted by female aedes mosquitoes infected with one of four dengue viruses (DENV1- DENV4). SEIR compartmental model is used to examine the transmission of the disease in the present work. The model has four compartments for the human population, susceptible, exposed, infected, and recovered and also four compartments for the mosquito population immature, susceptible, exposed, and infected. The impact of temperature on the dynamics of dengue disease transmission is described by this model. The basic reproduction number of the model is computed by implementing the Next Generation Matrix Method. Sensitivity analysis is performed to establish the relative importance of the model parameters and mathematical results are shown graphically.